Perceived Support of Sports Tourism in Pakistan: Evidence from the Residents of Karachi and Lahore After Initiation of Pakistan Super League (PSL) - Shaikh, Sadia; Sultan, Muhammad Faisal (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to investigate the perceived impact of economic, social, environmental, and cultural factors on the support towards sports tourism. The study utilizes subjective analysis technique and uses closed ended questionnaire, adopted from prior studies. The sample of the study has been taken from direct observers of sports tourism in Pakistan i.e. residents of Karachi and Lahore to assure the reliability of the results. Hence the data has been gathered through convenience sampling from a sample size of 3134 respondents. To analyze the results, AMOS software has been used. Results of the study posited that economic, social, and environmental factors produce favorable effects towards support of sports tourism in Pakistan although cultural factors do not produce any positive supportive impact towards sports tourism in the country. Study also uses terrorism as the moderating variable as several prior studies suggested terrorism as one of the major variables that can influence growth of business. Analogous results have been found in the study results that moderation of terrorism has diminished the impact of economic and social factors on support towards sports tourism.